Quatro décadas de resistência queer: artivismo LGBTI na Amazônia brasileira - Mílton Ribeiro; José Luiz de Moraes Franco (Cahiers des Amériques Latines, 2021)
The focus of this article is the LGBTI political mobilization in the Paraense Amazon, in view of their historical and cultural dimensions over the past four decades. In opposition to the narratives that locate the emergence of the LGBTI Movement in Brazil in the south/southeast axis, we suggest a quite different reading, by identifying the Festa da Chiquita and the Baile Gala Gay based in Belém and Abaetetuba (Pará) as being the hub of these disputes; in addition to the visit of anthropologist Peter Fry to the capital of Pará. The intention is to establish the Amazon region as a space of LGBTI resistance and artivism that has generated reflections on rights, visibility and respect for differences both inside and outside academia since the 1970s.